Determinants of consumer behaviour when choosing between whole and skimmed UHT milk - Siqueira, Kennya Beatriz; de Pinho, Marielli Cristina; Borges, Cristiano Amâncio Vieira; da Gama, Marco Antonio Sundfeld (Serbian Journal of Management, 2019)
Large amounts of UHT milk are consumed in Brazil, but little is known about the factors affecting the consumer’s decision to choose between whole and skimmed UHT milk. Since consumers represent one of the main market drivers, it is important to identify the factors influencing their behavioral patterns. A structured questionnaire was applied to 248 people in Juiz de Fora, Brazil. A binary logistic regression model was used to analyze the probability of buying whole or skimmed UHT milk. Results indicated that income, age, and number of family members in a residence are the major determinants of consumer behaviour when choosing between whole and skimmed milk. Higher income, older people, and smaller number of residents were associated with an increased consumption of skimmed milk. These results could be useful to orientate local dairy market campaigns and logistic distribution of products according to consumer preferences.